Factors affecting university image among undergraduate students: the case study of qatar university - Khalifa Alhaza (21259496) (2021)
Worldwide there is an increase in competition between higher education institutions seeking to ascertain their position in the world ranking, resulting in universities introspectively reflecting on their image and student satisfaction. This is especially the case in the Gulf Cooperation Countries, where there has been significant growth in higher education institutions. This study examines the factors that influence Qatar University’s image among undergraduate students and predicts factors impacting students’ satisfaction, influencing the university’s image. Results from 2,618 students’ responses to a 57-item student satisfaction questionnaire indicate that the university’s services are factors that influence students’ view of QU, and the students’ satisfaction directly contributes to a positive perception of Qatar University. The impact of university services on students’ perception of QU is further discussed based on gender, nationality, student classification, and major. Other Information Published in: Cogent Education License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/2331186x.2021.1977106